A 3D-IFU model for characterising the pore structure of hybrid fibre-reinforced concrete. (March 2020) - Niu, Ditao; Li, Dan; Fu, Qiang
Abstract: Intermingled fractal unit (IFU), composed of many fractal units with different fractal characteristics and geometries, is used to reconstruct the pore fractal characteristics of porous materials. In this paper, a three-dimensional (3D)-IFU model for characterising the pore structure of hybrid basalt-polypropylene fibre-reinforced concrete (HBPRC) was developed, and the applicability of this model was verified by test results. The results indicated that the volume fraction of the macropore (≥100 nm) of HBPRC increases with the addition of fibres. The higher fibre content causes a larger volume fraction of the macropore. Moreover, the lower matrix strength of concrete causes a more significant effect of fibres on the macropore of HBPRC. Compared with other fractal models, the 3D-IFU model not only has excellent simulation capability for cumulative porosity distribution and pore size distribution but also has high fitting accuracy for the total porosity, critical pore size and threshold porosity of HBPRC. Furthermore, the fractal dimension of the pore size distribution, derived from the 3D-IFU model, well reflects the effect of fibres on the pore structure characteristics of HBPRC. Graphical abstract: Unlabelled Image Highlights: The addition of basalt fibre and polypropylene fibre increases the volume fraction of the macropore (≥100 nm) of hybrid basalt-polypropylene fibre-reinforced concrete, and this effect increases with the decreasing concrete matrix strength. According to the construction process of Menger sponge and in the light of the construction principle of intermingled fractal unit, a 3D-IFU model is established to characterise the pore fractal characteristics of concrete. The developed 3D-IFU model has excellent simulation capability for the cumulative porosity distribution, pore size distribution, total porosity, critical pore size and threshold porosity of HBPRC. The pore size distribution fractal dimension derived from the 3D-IFU model well reflects the effect of fibres on the pore structure characteristics of hybrid basalt-polypropylene fibre-reinforced concrete.